2021
DOI: 10.1177/03635465211049219
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Impairs Enthesis Healing After Rotator Cuff Repair in a Rat Model

Abstract: Background: Being overweight or obese is associated with poor outcomes and an increased risk of failure after rotator cuff (RC) surgery. However, the effect of obesity on enthesis healing has not been well characterized. Hypotheses: Diet-induced obesity (DIO) would result in inferior enthesis healing in a rat model of RC repair, and a dietary intervention in the perioperative period would improve enthesis healing. Study Design: Controlled laboratory study. Methods: Male Sprague-Dawley rats were divided into 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
(106 reference statements)
0
8
1
Order By: Relevance
“…High circulating concentrations of adipokines may be acting as a prolonged disruptor of tendon healing in obese patients (14,15,25,39). A recent animal study reported leptin levels, an adipokine, were negatively correlated with load to failure and worse histological structure of the repaired tendon-bone interface after rotator cuff surgery (40). However, in this current study, no significant correlation was found between patient BMI and tenocyte growth, collagen production or gene expression profile.…”
Section: Discussioncontrasting
confidence: 68%
“…High circulating concentrations of adipokines may be acting as a prolonged disruptor of tendon healing in obese patients (14,15,25,39). A recent animal study reported leptin levels, an adipokine, were negatively correlated with load to failure and worse histological structure of the repaired tendon-bone interface after rotator cuff surgery (40). However, in this current study, no significant correlation was found between patient BMI and tenocyte growth, collagen production or gene expression profile.…”
Section: Discussioncontrasting
confidence: 68%
“…In the previous study using this animal cohort [ 25 ], a HFD led to increased body and fat mass, and impaired enthesis healing after rotator cuff repair surgery, with inferior biomechanical and histological outcomes. Restoring normal weight with dietary change after surgery did not improve healing outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We found some evidence to support this with some of the higher gene expression observed in the HFD group not found in the HF-CD group. However, in our first study on this animal cohort investigating tendon healing after rotator cuff surgery, changing from a HFD to CD peri-operatively did not improve healing outcomes [ 25 ]. Interestingly, in this study the adipose CM from animals in the HF-CD group had significantly higher expression of pro-inflammatory Il-1β than all other groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations